Retrocaval ureter: a rare cause of intermittent right flank pain in a 37 years old lady - Shoaib Rafique (Journal of the Pakistan Medical Association, 2022)
A 37 years old female presented with 6 months history of intermittent right flank pain. She was otherwise fit and had no other complaints. Her lab investigations were normal. Abdominal ultrsonography revealed moderate hydronephrosis and proximal hydroureter but no calculus. Retrograde ureteropyelography findings were consistent with the diagnosis of retrocaval ureter, a rare clinical condition. Surgical exploration confirmed the presence of right retrocaval ureter. The ureter was transected and transposed anterior to inferior vena cava and ureteropelvic anastomosis was performed. Postoperative recovery was uneventful. Keywords: Retrocaval ureter, hydronephrosis, ureter, ureteropelvic junction obstruction.